Local optimal control synthesis in the systems with delayed action - Degtyarev, G.L.; Terent'yev, S.A. (Zielona Góra: Uniwersytet Zielonogórski)
This study is devoted to the problems of optimal control synthesis in stochastic delayed action systems on the basis of the local quality criteria, characterizing the current precision of stabilization of the controlled motion.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka